Destructive Cholangitis in an Adult Jack Russell Terrier - Atsushi Kodama; Hiroki Sakai; Tsuyoshi Kimura; Sadatoshi Maeda; Takashi Mori; Toshiaki Masegi; Tokuma Yanai (Case Reports in Veterinary Medicine)
A 4-year-old female Jack Russell terrier dog exhibited vomiting and severe jaundice of the visible mucous membranes and skin. Ultrasonography revealed diffuse areas of high echogenicity and focal areas of low echogenicity in the left lobe of the liver. On macroscopic observation of the biopsied liver specimen, many scattered irregularly shaped red spots were observed on the liver surface and on the cut surface. Histopathologically, there was loss of the interlobular bile duct and cholangitis accompanied by infiltration of pigment-laden macrophages in the Glisson’s capsule. Therefore, in the present case the dog was diagnosed with destructive cholangitis.